An investigation into the bioactivity of Sutherlandia frutescens (Cancer bush) - Egbichi , Ifeanyi M. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2009.